MY SAY: Replacing foreign maids with local home managers - Abd Razak, Dzulkifli (2010)
About a year ago, this column highlighted issues related to foreign maids in the country. The main concern was how they were being mistreated by their employers. Some were virtually turned into slaves. Although this involved only a handful of ugly Malaysians, the cases that were made public were highly explosive due to their barbaric nature. Malaysia earned a bad reputation with respect to human rights in the international arena. The distinction between the role of a regular house helper and a professional home manager was also highlighted, suggesting that the latter was preferable if employers insisted on a competent worker.